Vector Development Timeline for Mucosal Vaccination and Treatment of Disease Using Lactococcus lactis and Design Approaches of Next Generation Food Grade Plasmids - de Castro, Camila Prosperi; Drumond, Mariana M.; Batista, Viviane L.; Nunes, Amanda; Mancha-Agresti, Pamela; Azevedo, Vasco (Frontiers in Microbiology, 2018)
Lactococcus lactis has been used historically in fermentation and food preservation processes, they are considered safe for human consumption (GRAS- Generally Recognized As Safe). Nowadays, in addition to its wide use in food industry, L. lactis has been used as a bioreactor for the production of molecules of medical interest, as well as vectors for DNA delivery. These applications are possible due to the development over the last decades of promising genetic tools, such as gene expression, protein targeting systems and vaccine plasmids. Thus, this review presents some of these genetic tools and their evolution, which allow us to envision new biotechnological and therapeutic uses for L. lactis. Constitutive and inductive expression systems will be discussed, many of which have been used successfully for heterologous production of different proteins, tested in animal models. In addition, advances in the construction of new plasmids to be used as potential DNA vaccines, delivered by this microorganism, will also be viewed. Finally, we will focus on the scene of gene expression systems known as "food-grade systems" based on inducing compounds and safe selection markers, which eliminate the need for use of compounds harmful to humans or animal health and potential future prospects for their applications.